KAIDAH-KAIDAH WALI DALAM PERNIKAHAN: Analisa Perpindahan Hak Wali Dalam Pernikahan - Misbachul Fitri, Abdul Basit; Miftahuddin , Abdul Hafidz (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
According to Imam Malik and Imam Shafi'i, the wali nikah (guardian of marriage) is one of the pillars of marriage. According to Abu Hanifah, the wali who must be present in the marriage contract as mentioned in the hadith above is only required if the bride is not yet baligh (mature) or not of sound mind. A woman who has reached maturity and is of sound mind is allowed to marry a man she likes without a wali, provided that he is sekufu (compatible). Imam Malik, according to the Asyhab tradition, believes that marriage without a wali is valid. The order of guardians in marriage is first the wali mujbir, second the wali hakim, and third the wali muhakkam. In essence, a woman should be married by her father who acts as her guardian, but sometimes a father refuses to act as a guardian for his child. Although there are different levels of guardianship, if the transfer is due to the guardian's reluctance to marry his child under his guardianship, then the level of guardianship is no longer valid so that the transfer of the right to marry goes directly to the wali hakim.